2020
DOI: 10.1002/jcph.1696
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Exposure‐Response Relationship of Luspatercept, an Erythroid Maturation Agent, in Anemic Patients With β‐Thalassemia

Abstract: β-Thalassemia is an inherited blood disorder resulting from defects in hemoglobin production, leading to premature death of red blood cells (RBCs) or their precursors. Patients with transfusion-dependent β-thalassemia often need lifelong regular RBC transfusions to maintain adequate hemoglobin levels. Frequent transfusions may lead to iron overload and organ damage. Thus, there is a large unmet need for alternative therapies. Luspatercept, a first-in-class erythroid maturation agent, is the first approved ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It is well known that GATA-1 is indispensable for erythroid maturation. 18,19 A recent article by Chen et al 20 showed that the mean elimination half-life of luspatercept is ;11 days.…”
Section: Luspatercept Pharmacologymentioning
confidence: 99%
“…It is well known that GATA-1 is indispensable for erythroid maturation. 18,19 A recent article by Chen et al 20 showed that the mean elimination half-life of luspatercept is ;11 days.…”
Section: Luspatercept Pharmacologymentioning
confidence: 99%
“…The recommended doses for thalassaemia patients are 1 or 1.25 mg/Kg, administered subcutaneously every 21 days. As confirmed by pharmacokinetic studies, this dosing scheme allows a stable plasma concentration to be reached over time, independently of factors such as age, sex, ethnicity, or renal or hepatic impairment [67]. Parallelly, a phase 2, double-blind, placebo-controlled trial of luspatercept in NTDT (NCT03342404) recently completed the blinded phase [68].…”
Section: Luspatercept (Ace-536)mentioning
confidence: 99%
“…Luspatercept was approved via the Food and Drug Administration (FDA) on November 8, 2019 [ 10 ]. It was also authorized in 2020 via the European Medicines Agency [ 11 ]. Luspatercept was used to cure β-thalassemia and treat myelodysplastic syndrome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%